Studi Kasus: Penerapan Sistem Pembayaran Digital pada Pelaku UMKM di Kampung Wisata Sukadiri (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
The development of digital technology has brought significant changes to economic transaction systems, including the Micro, Small, and Medium Enterprises (MSMEs) sector. Digital payment systems are one of the innovations that can help MSMEs improve the convenience, speed, and efficiency of transaction processes. This study aims to analyze the implementation of digital payment systems among MSME actors in Sukadiri Tourism Village and to identify the benefits, challenges, and level of acceptance of digital payment methods in their business activities. This study employs a descriptive approach using a case study method. Data were collected through observation, interviews, and documentation involving MSME actors operating in Sukadiri Tourism Village. The results of this study are expected to provide an overview of the utilization of digital payment systems in supporting MSME transaction activities, particularly in improving payment convenience and expanding transaction method options for consumers. Furthermore, this study is expected to serve as an evaluation and reference for MSME actors and relevant stakeholders in enhancing the utilization of digital payment technology as part of efforts to support digital transformation and economic development in Sukadiri Tourism Village.